Profiling GPS users among small scale fishermen in Malaysia - Mohamed Shaffril, Hayrol Azril; Hamzah, Azimi; Abu Samah, Bahaman (Human Resource Management Academic Research Society, 2017)
This study aims to profile the GPS users among small scale fishermen in Malaysia. The study is quantitative in nature whereby a total of 400 respondents from 12 fisheries districts were involved. The analysis have confirmed that older fishermen with PMR/SRP level of education formed the majority of GPS users. On average, the fishermen surveyed had about 19 years of experience in fishing activities and they have utilised the GPS for 5 years. Their level of GPS usage was high and in general, most of them has been relying on this technology for two main purposes – navigation and safety. The findings from this study can assist the concerned parties in understanding the background of GPS users and their pattern of usage, which later allows them to strategize several efforts to encourage GPS usage among non-users through future programs that are in line with their needs, abilities and interests.